Work Transformation Of Women Towards Family (Case Of Women Workers At PT. Spice Island Hatusua Village, Kairatu District, Seram Bagian Barat District) - Nathalia M Keisera; Junianita F Sopamena; Felecia P Adam (Cita konsultindo, 2023)
This study aims to analyze the transformation of women's work at PT. Spice Island Hatusua Village and analyze the driving factors and impacts of the transformation of the work of women workers at PT. Spice Island Hatusua Village. The research location was chosen purposively (purposive random sampling). The population in this study were all casual daily workers at PT. Spice Island Maluku, totaling 74 people. Sampling is based on Arikunto's research considerations. If the total population is less than 100 people, the total sample is taken as a whole, but if the population is greater than 100 people, then 10-15% or 20-25% of the total population can be taken. Based on this research, because the total population is not greater than 100 respondents, the authors take 100% of the population at PT. Spice Island, namely as many as 18 female THL people. Thus the use of the entire population without having to draw a research sample as a unit of observation is referred to as a census technique. The research method uses descriptive qualitative. The results of the research show that the village of Hatusua has undergone work transformation after the cooperation between the community and PT. Spice Island Maluku (SIM) which made a change for the whole community of Hatusua Village, especially for housewives.